Merchandise Sebagai Media Promosi Perilisan Game Voltshadow - Albert Champan Hadikusumo (Penerbit dan Percetakan, CV. Picmotiv, 2025)
The rapid growth of the global game industry presents unique challenges for independent developers in effectively marketing their products. One case example is Voltshadow, a mobile game developed by the local indie studio Itiak Games, which, despite its promising visual and narrative quality, has received limited public attention due to a lack of promotional media. This study aims to design a promotional strategy through merchandise as a form of visual communication capable of increasing awareness and appeal toward Voltshadow. The research was conducted using qualitative methods, including interviews with professionals in illustration and merchandise design, observation of merchandise trends in both local and international game industries, and literature studies from various academic sources. As a result, a series of merchandise products were designed to not only represent the visual identity of Voltshadow but also build an emotional connection with the audience. The merchandise design implementation includes aspects such as illustration, color, typography, and the strategic placement of visual elements tailored to the characteristics of the target market. This design is expected to serve as an effective solution to support the release of indie games and strengthen Voltshadow's position in both the national and global game industries.